THU0150 FINGER JOINT CARTILAGE EVALUATED BY ULTRASOUND IN PATIENTS WITH RHEUMATOID ARTHRITIS AND HEALTHY SUBJECTS. (June 2019) - Ogura, Takehisa; Hirata, Ayako; Hayashi, Norihide; Ito, Hideki; Takenaka, Sayaka; Inoue, Yuki; Kagtagiri, Takaharu; Imaizumi, Chihiro; Takakura, Yuto; Kameda, Hideto
Abstract : Background: Joint destruction in rheumatoid arthritis (RA) includes both bone and cartilage lesions. Since joint space narrowing (JSN) is not a direct evaluation of cartilage using X-ray, we aimed to examine the validity of ultrasound (US) cartilage evaluation in patients with RA. Objectives: Methods: The cartilage thickness of bilateral metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joints of the 2nd to 5th fingers were visualized from a dorsal view with joints in approximately 90 degrees flexion and measured at the middle portion. Furthermore, one US examiner performed the semiquantitative scoring of the recorded cartilage images in a blinded manner on a scale of 0–2. In addition, the JSN of the corresponding joints was scored using the van der Heijde-modified Sharp method with a hand X-ray. Continuous variables were analysed using the Mann–Whitney U test. The relationships among the total measurement of cartilage thickness, its semi-quantitative score, and the JSN score were assessed using Spearman's rank correlation coefficients. Results: One hundred and three patients with RA and 42 healthy subjects were enrolled in this study. The total cartilage thickness was significantly thinner in patients with RA compared to healthy subjects for both the MCP and PIP joints (both p<0.001). The semi-quantitative sum of 16 joints ranged from 2 to 26 (median 8) in patients with RA, which was significantly greater than the 0 to 11 (median 4) seen in healthy subjects (p<0.001). In patients with RA, the semi-quantitative score showed a significant negative correlation with cartilage thickness (rho=−0.64; p<0.001) as well as a significant positive correlation with JSN score (rho=0.66; p<0.001). In addition, in healthy subjects, semi-quantitative score, but not cartilage thickness was significantly correlated with age (rho=0.49; p=0.001 and rho=–0.25; p=0.118, respectively). On the other hand, in RA, these scores showed a significant correlation with RA disease duration but not correlated with age. Conclusion: A simplified and direct evaluation of finger joint cartilage damage by semi-quantitative US score is valid and useful for patients with RA. Disclosure of Interests: Takehisa Ogura: None declared, Ayako Hirata: None declared, Norihide Hayashi: None declared, Hideki Ito: None declared, Sayaka Takenaka: None declared, Yuki Inoue: None declared, Takaharu Kagtagiri: None declared, Chihiro Imaizumi: None declared, Yuto Takakura: None declared, Hideto Kameda Grant/research support from: AbbVie, Asahi Kasei Pharma, Astellas, Chugai, Eisai, GlaxoSmithKlein, Mitsubishi-Tanabe, Novartis, Consultant for: AbbVie, Eli Lilly, Novartis, Speakers bureau: AbbVie, Asahi Kasei Pharma, Bristol-Myers, Chugai, Eli Lilly, Janssen, Mitsubishi-Tanabe, Novartis, Pfize